Perspektif Kesejahteraan Pekerja dengan Model Employee Branding dalam Perusahaan - Wijaya, Aditya Rizky; Ambarwati, Mega Dewi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Employee branding is a strategy that makes workers ambassadors or representatives of the company, both inside and outside the work environment. This article discusses the perspective of employee welfare through the implementation of employee branding. The focus is on the benefits received by workers, both psychologically, financially, and socially, as well as the challenges they face. This article also reviews company support to ensure the success of employee branding programs.